(untitled) (ENTHYMEMA, 2009)
The article proposes some reflections on playing and literature. The first section deals with the definition of «playing» and «literature» and it outlines some similarities between the strucutures of the two categories. The second section introduces some functions and some aspects of playing – learning, amusement, ritual socialization, freedom and alterity –, by combining hints from ethology, psychology, anthropology and philosophy. Finally, the third section focuses on literature and on the reader’s experience in particular, by comparing them with playing in relation to the functions and aspects previously noted.